2017
DOI: 10.35789/fib.bull.0081.ch14
|View full text |Cite
|
Sign up to set email alerts
|

Structural robustness of concrete flat slab structures

Abstract: Current building regulations for design against progressive collapse normally use prescriptive rules and riskbased qualitative scales which are insufficient to cover current needs in design. Structural robustness of concrete flat slab structures is examined using different theoretical models to capture the dynamic behavior under accidental events. In such extreme events, the large dynamic reactions at the connections could potentially lead to punching and progressive collapse. Punching formulae based on load-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
2
14
0
1
Order By: Relevance
“…The values of the dynamic amplification of the load obtained in this work (DAFLF = 1.24) are also consistent with test results of sudden corner column removal by Qian and Li [40] in which they report dynamic load increase factors between 1.13 and 1.23. These results are also comparable with dynamic amplification factors for internal column removal obtained experimentally [47], numerically [9] or theoretically [12] which can vary between 1.6 and 1.2.…”
Section: Evaluation Of Dynamic Amplification Factors (Dafs)supporting
confidence: 88%
See 1 more Smart Citation
“…The values of the dynamic amplification of the load obtained in this work (DAFLF = 1.24) are also consistent with test results of sudden corner column removal by Qian and Li [40] in which they report dynamic load increase factors between 1.13 and 1.23. These results are also comparable with dynamic amplification factors for internal column removal obtained experimentally [47], numerically [9] or theoretically [12] which can vary between 1.6 and 1.2.…”
Section: Evaluation Of Dynamic Amplification Factors (Dafs)supporting
confidence: 88%
“…threat-dependent approaches) [9,10]; and b) those that only attempted to minimise the consequences of a local failure, whatever its cause (i.e. threat-independent approaches) and avoid the failure spreading to other elements in the building [5,11,12]. Within this latter group, diverse numerical and experimental studies have analysed the structural response of buildings subjected to column removal as recommended in most current codes [13][14][15].…”
Section: Some Events With a High Impact Amongst The Engineering Commumentioning
confidence: 99%
“…Tying is generally provided through horizontal and vertical ties achieved by prescribing a minimum tying force requirement, which are generally consistent within the different codes shown in Table 5, except for IBC 2009 [46] that provides lower tying forces [55]. Research on the efficiency of tying to different types of construction including steel and concrete structures showed that the rotations required in the connections to form a pure tensile membrane that arrests progressive collapse are unachievable in some cases [63,[73][74][75][76]. In order to address this issue, some codes such as UFC 4-023-03 [45] have included rotation limits on their tying force requirements for different forms of construction.…”
Section: Review Of Design Methods Against Progressive Collapsementioning
confidence: 67%
“…The probability of occurrence of each cause was quantified in direct proportion to the number of times the cause was cited or appeared in the different accident reports studied in the previous work [10]. The local failure scenarios considered followed the conventional notional member removal approach used traditionally for permanent structures to assess whether the structure can develop alternative load paths after local damage [16,20,26,27,39,40]. The aim of this study was to determine the effects of sudden failure of one or more ground-floor shores, which carry the highest loads when the third floor is poured, with two cleared floors and one fully shored.…”
Section: Local Failure Scenarios and Resultsmentioning
confidence: 99%